2002
DOI: 10.1080/00365510260296564
|View full text |Cite
|
Sign up to set email alerts
|

Butyrylcholinesterase activity and risk factors for coronary artery disease

Abstract: The aim of this study was to verify which risk factors for coronary artery disease (CAD) are independently correlated with butyrylcholinesterase (BChE) activity. We studied 88 White individuals (43 males) aged 47.3+/-15.7 years (mean+/-SD; range: 14.0-80.0 years) including 38 with hyperlipidemia, 30 with hypertension and 5 with diabetes mellitus (DM). Simple correlation analysis showed that BChE activity was positively correlated with age, sex, body mass index, hypertension and DM, as well as with triglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 27 publications
7
49
0
1
Order By: Relevance
“…The negative influence of male gender related to low BuChE levels likely reflects the fact that most of the chlorpyrifos exposed workers were males. Studies exist in which simple correlational analyses associated BuChE activity with sex and a number of other factors related to coronary artery disease, but step-wise multiple regression analysis did not show independent correlations with BuChE activity (Alcantara et al, 2002). Cross-sectional evaluations of the possible role of BuChE activity in Alzheimer disease (as related to the introduction of anticholinesterase treatments) and cardiovascular disease found that BuChE activity was inversely associated with age, positively associated with being overweight and obese (e.g., BMI), and positively associated with serum albumin, cholesterol, and triglyceride levels (Calderon-Margalit et al, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…The negative influence of male gender related to low BuChE levels likely reflects the fact that most of the chlorpyrifos exposed workers were males. Studies exist in which simple correlational analyses associated BuChE activity with sex and a number of other factors related to coronary artery disease, but step-wise multiple regression analysis did not show independent correlations with BuChE activity (Alcantara et al, 2002). Cross-sectional evaluations of the possible role of BuChE activity in Alzheimer disease (as related to the introduction of anticholinesterase treatments) and cardiovascular disease found that BuChE activity was inversely associated with age, positively associated with being overweight and obese (e.g., BMI), and positively associated with serum albumin, cholesterol, and triglyceride levels (Calderon-Margalit et al, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…However, the DM2 subjects presented higher values for a majority of the analyzed variables, except for height, HDL-C and AC OF . The pairing procedure was used because males and older individuals presented higher mean values for BChEA (4,7,9,33,34), AC 4/5 (4,34) and AC OF (4), when compared to females and younger individuals with CHE2 C5-phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…The physiological function of BChE is still unknown, but positive correlations were found between BChEA and diabetes mellitus (DM) (6,7); triglycerides (TG) (7)(8)(9); total cholesterol (TC) (7,10); apolipoprotein B (ApoB) (7,9); adult body weight (2,11) and BMI (3,4). In light of some of these correlations, Kutty and cols.…”
Section: Introductionmentioning
confidence: 99%
“…Positive correlations between total BChE activity and total cholesterol levels have already been shown. 6,18,23 An increase in total BChE activity has already been detected in hyperthyroidism. 24,25 The negative correlation with E 2 is supported by data showing higher mean total BChE activity in men than in women in the fertile period, a difference that disappears after menopause.…”
Section: Discussionmentioning
confidence: 97%